The role of science curricula in providing health's concepts awareness for students of the first cycle of basic education from the point of view of teachers and educational supervisors - sbera, Fouaad; sultan, Manal; msto, Maryana (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The purpose of this research is to define the role of science curricula in Providing health's concept awareness to the students of the first cycle of basic education from the point of view of teachers and educational supervisors. The research adopted the descriptive analytical method by designing a questionnaire consisting of two axes: evaluation of the science curricula for health awareness, degree of availability of concept related to health awareness. The research sample was consisted of (71) teachers and assistant teachers / specialized in science / (26) educational supervisors , the most important results of the research were: -The evaluation degree of the science curricula for the first cycle for health awareness is medium . -The availability of concepts related to food awareness and environmental awareness was moderate, while the concepts of the body care and appearance were high, but the concept of right health practices were low. -There are no statistically significant differences between the responses average of the educational supervisors and the responses average of the teachers and the assistant teachers regarding the role of the science curricula in providing the health's concept awareness for the students of the first cycle of basic education. -There are differences between the responses average degrees of the sample of the research in relation to the role of science curricula in providing the health's concept awareness for students of the first cycle of basic education according to the variable participation in training courses on developed curricula, for the participants in these courses. -There are no differences between the responses average degrees of the sample of the research sample in relation to the role of science curricula in providing the health's concept awareness for students of the first cycle of basic education according to the variable number of years of experience.